2016
DOI: 10.1523/jneurosci.2051-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Potentiation at the Mossy Fiber–Granule Cell Relay Invokes Postsynaptic Second-Messenger Regulation of Kv4 Channels

Abstract: Mossy fiber afferents to cerebellar granule cells form the primary synaptic relay into cerebellum, providing an ideal site to process signal inputs differentially. Mossy fiber input is known to exhibit a long-term potentiation (LTP) of synaptic efficacy through a combination of presynaptic and postsynaptic mechanisms. However, the specific postsynaptic mechanisms contributing to LTP of mossy fiber input is unknown. The current study tested the hypothesis that LTP induces a change in intrinsic membrane excitabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 53 publications
4
25
1
Order By: Relevance
“…Nav1.6 labeling appears consistent with somatic and axonal initial segment localization 35,42 , which aligns with previous reports using the same antibody 73,74 . Kv4.3 labeling is consistent with somatic localization in layer V pyramidal neurons 75 , and corresponds with validated labeling in hippocampal CA3 neurons using the vendor antibody 76 . Finally, Kv7.2 labeling appears to be expressed in axons and synaptic terminals 62,63 , where our specific antibody has been confirmed with heavy colocalization in the Nodes of Ranvier 77 .…”
Section: Discussionsupporting
confidence: 77%
“…Nav1.6 labeling appears consistent with somatic and axonal initial segment localization 35,42 , which aligns with previous reports using the same antibody 73,74 . Kv4.3 labeling is consistent with somatic localization in layer V pyramidal neurons 75 , and corresponds with validated labeling in hippocampal CA3 neurons using the vendor antibody 76 . Finally, Kv7.2 labeling appears to be expressed in axons and synaptic terminals 62,63 , where our specific antibody has been confirmed with heavy colocalization in the Nodes of Ranvier 77 .…”
Section: Discussionsupporting
confidence: 77%
“…Thus, our data show that KChIP3 and KChIP4 were expressed in the same neuronal populations as Kv4.2 and Kv4.3, and this included PCs and GCs. The present findings are in agreement with previous studies showing that the mRNA and protein for KChIP3 and KChIP4 are distributed in PCs and GCs [ 19 , 22 ], two neuron populations that also express Kv4.2 and Kv4.3 transcripts and proteins [ 22 , 23 , 28 , 29 , 30 ]. Interestingly, our single-label immunoperoxidase immunohistochemistry also showed that only KChIP3 and Kv4.3 were found in interneurons (basket and stellate cells) in the molecular layer, suggesting that some cerebellar neurons also show differential association between KChIPs and Kv4.…”
Section: Discussionsupporting
confidence: 94%
“…Because there are few published high-resolution immunoelectron microscopic and electrophysiological data showing the precise localisation of KChIP and Kv4 subunits in the cerebellum, it is difficult to draw conclusions about the functional significance of our results at present. On the basis of previous and present results, one possibility is that Kv4 and KChIP are related with LTP at the mossy fibre–granule cell, known to be regulated by Kv4 channels [ 30 ]. Given that this LTP has also been attributed to presynaptic mechanisms [ 45 ], further electrophysiological studies will be essential to unravel a specific role carried out by KChIP and Kv4 α subunits channels located at axon terminals.…”
Section: Discussionmentioning
confidence: 92%
“…However, whether these neuronal networks perform a 50 Fourier-like transform on their inputs remains unknown. 51 between lobule V and IX differed (Figure 1-figure supplement 1), consistent 125 with previously described differences in, e.g., the firing frequency in vivo between 126 these two lobules (Witter and De Zeeuw, 2015a;Zhou et al, 2014) and in the 127 differential density of Kv4 and Cav3 channel expression in GCs across different 128 lobules (Heath et al, 2014;Rizwan et al, 2016;Serôdio and Rudy, 1998). Taking 129 the large functional difference between spino-and vestibulo-cerebellum into 130 account (Witter and De Zeeuw, 2015b), these data suggest that different 131 biophysical properties of GCs is likely a conserved mechanism throughout the 132 entire cerebellar cortex, potentially tuning GCs to different frequencies.…”
Section: Introduction 35supporting
confidence: 79%